A program for the treatment of nocturnal enuresis - Konakçı, H. Sühendan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1982., 1982)
Enuresis is a well-known problem of childhood. Although it has a long history of incidena, a method which leads to permanent cure has not been found yet. The present study attempts to investigate the effectiveness of a treatment program developed for nocturnal enuretic children. The notable feature of the program is that it involves both psychodynamic a behavioristic principles. Eighteen children mo were between the ages of 4 and 12 were used in the study. There were 8 males and 8 females . The treatrrent was given to one group of children while it was withheld from a control group. It was hypothesized that there will be a significant decrease in the number of bedwettings in the treatrrent group, compared to the control group. The results obtained from the treatment group were compared with the spontaneous recovery rate of the ccntrol group. The treatment group shaved a significant decrease. Since, six months later, relapse was observed in a number of subjects, some factors should be given more consideration in the application of the proposed program.
Keywords: Enuresis.; Pediatric urology.; Child psychology.